Vasopressin and oxytocin excite BNST neurons via oxytocin receptors, which reduce anxious arousal - Francesconi, Walter; Olivera-Pasilio, Valentina; Berton, Fulvia; Olson, Susan L.; Chudoba, Rachel; Monroy, Lorena M.; Krabichler, Quirin; Grinevich, Valéry; Dabrowska, Joanna (Cell reports, 2025)
Interoceptive signals dynamically interact with the environment to shape appropriate defensive behaviors. Hypothalamic hormones arginine-vasopressin (AVP) and oxytocin (OT) regulate physiological states, including water and electrolyte balance, circadian rhythmicity, and defensive behaviors. Both AVP and OT neurons project to the bed nucleus of stria terminalis (BNST), which expresses OT receptors (OTRs) and vasopressin receptors, and governs fear responses. However, understanding the integrated role of AVP and OT is complicated by their cross-reactivity and their mutual receptor promiscuity. Here, we provide evidence that the effects of neurohypophysial hormones on BNST excitability are driven by cell-type-specific receptor selectivity and input specificity. We show that OTR-expressing BNST neurons, excited by hypothalamic AVP and OT inputs via OTR, play a major role in regulating BNST excitability, overcoming threat avoidance, and reducing threat-elicited anxious arousal. Therefore, OTR-BNST neurons are perfectly suited to drive the dynamic interactions balancing external threat risk and physiological needs.
Online verfügbar: 3. Juni 2025, Artikelversion: 3. Juni 2025
Gesehen am 25.09.2025